Characterisation of the antifungal effects of a plant-based compound, CIN-102, on the main septal filamentous fungi involved in human pathology. (June 2021) - D'Agostino, Maurine; Tesse, Nicolas; Lavergne, Rose Anne; Pape, Patrice Le; Bouchara, Jean Philippe; Frippiat, Jean Pol; Machouart, Marie; Debourgogne, Anne
Highlights: CIN-102 has antifungal activity against the genera Aspergillus, Scedosporium and Fusarium . The various strains tested had no phenotypes of resistance against CIN-102. CIN-102 shows an effect on spore germination and fungal growth. The post-antifungal effect is important with CIN-102. ABSTRACT: Objectives: Today, the increase of invasive fungal infections and the emergence of resistant strains are observed in medical practice. New antifungals are expected, and the plant world offers a panel of potentially active molecules. CIN-102 is a mixture of seven different compounds of plant origin developed from the formulation of cinnamon essential oil. Methods: The in vitro activity of CIN-102 was characterised against Aspergillus spp., Fusarium spp. and Scedosporium spp. by studying the minimum inhibitory concentration (MIC), inoculum effect, germination inhibition, fungal growth, post-antifungal effect (PAFE) and synergy. Results: MICs determined for the three genera followed a unimodal distribution and their mean values ranged from 62–250 μg/mL. CIN-102 demonstrated an inoculum effect similar to voriconazole and amphotericin B, 100% inhibition of spore germination and a PAFE. Conclusion: CIN-102 has significant activity against filamentous fungi involved in human pathologies and should be further explored as a potential new treatment. Other studies regarding its mechanisms of action as well as animal investigations are awaited.